MUSLIM LOYALTY AND IDENTITY IN EUROPE: Discourse Analysis of ECFR Fatwas - Belhaj, Abdessamad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
This article aims to study the European Council for Fatwa and Research (ECFR)’s fatwas and legal statements concerning Muslims’ loyalties to European states. the authoritative Sunni reformist scholarly institution arguments and theses in chronological order. Next, I will examine the resources and limitations of loyalty in the ECFR’s fatwas in relation to the European securitization of loyalty. Specifically, emphasis will be placed on how, in the European setting, loyalty to secular states and Islam can coexist, complement each other, or conflict. This article uses a discourse analysis method to examine the ethical assumptions in these fatwas while also contextualizing them in the current debates on politics and ethics, drawing on sociology of religious norms. The study shows that the discourses of the European Council for Fatwa and Research advocate the ideas of multiple loyalties and the harmony and complementarity of political citizenship with religious loyalty to Islam. These findings imply the commitment of Sunni reformism to political loyalty as a moral basis of group identification, the self and the other, and the processes of forming alliances and the quest for social cohesion.